ACUTE EFFECTS OF FOAM ROLLING AND PNF STRETCHING AS WARM-UP STRATEGIES ON MUSCLE FLEXIBILITY, STRENGTH, AND PRESSURE PAIN THRESHOLD IN AMATEUR ATHLETES - Elif Esma Bayraktar; Hayri Eren Yılmaz; Birce Beril Çelik; Mahmut Efe Bükülmez; Eren Çekiç (Karya Journal of Health Science, 2026)
Objective: This study aimed to compare the acute effects of foam rolling (FR) and proprioceptive neuromuscular facilitation (PNF) stretching on hamstring flexibility, isometric knee flexion strength, vertical jump performance, and pressure pain threshold (PPT) in amateur athletes.Method: Seventy-six amateur athletes were randomly allocated to either the FR group (n=36) or the PNF stretching group (n=40). Following a standardized 5-minute aerobic cycling warm-up, participants received either 3×30 seconds of unilateral hamstring FR or 4×30 seconds of PNF stretching consisting of 5 seconds of isometric contraction, 5 seconds of relaxation, and 20 seconds of passive stretching. Hamstring flexibility was assessed using the sit-and-reach test, isometric knee flexion strength using handheld dynamometry, vertical jump height using a standing vertical jump test, and PPT using pressure algometry. Outcomes were assessed before and immediately after the interventions.Results: Sit-and-reach performance increased significantly in both groups after the intervention (FR: Δ=1.81 cm, p